Local fiscal pressure, policy distortion and energy efficiency: Micro-evidence from a quasi-natural experiment in China. (1st September 2022) - Jiang, Wei; Li, Xitao; Liu, Ruoxi; Song, Yijia
Abstract: This study develops a stylized theoretical model wherein local fiscal pressure induces policy distortions and thereby reducing the energy efficiency (EE) in firms in the manufacturing sector. Combined with local government behavior and the response of firms, we propose two possible channels: the factor substitution effect and pollution compensation effect. To test theoretical predictions, with large and unique firm-level data, we adopt a difference-in-difference (DID) approach to identify the causal effect of local fiscal pressure on EE using the agricultural tax abolition reform of China as a quasi-natural experiment. The study finds robust and consistent evidence that severe local fiscal pressure caused by agricultural tax reform has significantly reduced the EE in firms in the Chinese manufacturing sector. Specifically, Chinese local governments spurred industrial development by distorting energy prices to ease fiscal pressure, which led to reduced EE through factor substitution. Pollution compensation reinforces the factor substitution effect, further worsening energy efficiency. Our findings are deemed robust after controlling for the parallel trend test, placebo test, influences of measurement error, and other estimation issues. Finally, we provide new and detailed policy implications for China's future fiscal system reforms and energy market reforms to avoid unintended consequences. Highlights: The reform of agricultural tax caused severe local fiscal pressure. Government have strong incentives to expand production and increase tax revenue. Energy price distortion leads to overuse of energy and lower energy efficiency. Fiscal pressure negatively impact the firms' energy efficiency. Energy efficiency loss is an unintended outcome of agricultural tax reform.